IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SUMMARIZING STRATEGY AT JUNIOR HIGH SCHOOL - Asty, Herfyna (Jurnal Pelangi : Research of Education and Development, 2013)
The observations showed that there were five problems faced by the students in reading comprehension class : (1) students were lazy to read English texts; (2) students fount difficulty to understand the contents of reading text because the have limited vocabulary; (3) students did not  have enough time because they have busy to consult the dictionary for any difficult words they found on the reading text; (4) the students were extremely passive during the class; and (5) the teaching technique used by the teacher was not interesting to the students.To solve the problems, a classroom action research of applying the summarizing strategy was conducted. The results showed that the application of the summarizing strategy to reading comprehension classes successfully improve students’ performance on reading comprehension tests. This success was confirmed by increasing average students score during cycle 1 to cycle 2. The average score during cycle 1 was 64.13, the average score during cycle 2 was 69.88, and that during cycle 3 was 72.38. Furthermore, students’ perceptions of the application of summarizing strategy to reading classes were also improving. These were supported by average percentages of positive perception of 40.5 in cycle 1, 73.9 in cycle 2, 84.6 in cycle 3.Thus, it was concluded that the summarizing strategy id effective to improve students’ reading comprehension. In addition, the strategy also enhances students’ perceptions of the application of the strategy to reading classes.